Environmental Life Cycle Assessment of small water resource recovery facilities: Comparison of mechanical and lagoon systems. (15th May 2022) - Thompson, Matthew; Moussavi, Sussan; Li, Shaobin; Barutha, Philip; Dvorak, Bruce
Highlights: Environmental impacts of 35 small water resource recovery facilities were assessed. Lagoons showed 12–50% of the environmental impact relative to mechanical systems. Per capita land use of lagoons was 30 times that of mechanical systems. Environmental impacts are sensitive to lifespan and type of electric grid mix. Uncertainty analyses revealed variability drivers within small systems. Abstract: Small water resource recovery facilities (WRRFs) serving communities with populations of less than 10, 000 people account for 70% of centralized wastewater treatment systems in the United States. With growing interest globally in improving the sustainability of these systems, this study evaluated the environmental life cycle impact and land use tradeoffs of different lagoon and mechanical WRRFs across the diverse climate of Nebraska. Life cycle inventory including construction and operations was collected for 35 existing systems representing a range of commonly used mechanical WRRFs: oxidation ditch, extended aeration, and sequencing batch reactors, and lagoon treatment systems: complete retention, irrigation, and controlled discharge lagoons. Lagoons exhibit a significantly smaller environmental impact relative to mechanical WRRFs in all impact categories with exception of the smog category based on a 20-year design lifespan provided land is available for use; in contrast, on-site land use of lagoons was significantly higher than mechanical WRRFs, 73.7 ± 35.9 m 2 /capita and 2.4 ± 1.9 m 2 /capita, respectively. Lagoons on average exhibited significantly more impact associated with the construction phase in most impact categories (up to 80% in case of smog impacts) relative to mechanical WRRFs (<25%). The differences in contribution of the construction leads to the environmental impacts and comparisons between the technologies being sensitive to system lifespan and type of electric grid mix. Irrigation lagoon per capita excavation and cast-iron resource use was observed to decrease with increasing differences between evaporation and precipitation rates. Uncertainty of the environmental impacts within sites is primarily driven by variations in energy intensity within mechanical WRRFs and volumes of treated water within lagoons. Variability between facilities of similar technology groups is largely driven by a combination of site-specific factors including climate, design, and operations. Graphical abstract: Image, graphical abstract